Causes, Consequences and Solutions to Environmental Problems from the Eyes of Preschool Children - Erdas-Kartal, Eda; Ada, Ezgi (ISRES Publishing, 2022)
This study is a case study that investigates the perceptions of preschool children about the causes, consequences, and solutions to environmental problems. A total of 41 children participated in the study. The data were obtained by using the draw and explain the technique, which included 3 different drawings and telling the children about the causes, consequences, and solutions of environmental problems. In the analysis of the data, the content analysis method was used. As a result of the research, it was found that the preschool children's perceptions were limited; however, as the age group grows, it has been determined that the icons used in the pictures related to the causes, consequences, and solutions of the environmental problems vary. It was revealed that the children associate the causes and consequences of environmental problems with pollution and the ways of solving environmental problems with the prevention/elimination of this pollution. It has been observed that the number of children related to the destruction of nature and irresponsible consumption of natural resources with environmental problems is very limited. In order to improve children's perceptions of environmental problems, it is suggested that teachers and parents should give more space to activities and games related to the environment in daily flow.
Keywords: Özel Eğitim ve Engelli Eğitimi; Environmental education; Environmental problems; preschool education; Special Education and Disabled Education; 13. Climate action; 4. Education